Effect of culture conditions on the production of phenols, total flavonoids and their antioxidant capacity in arnica (Heterotheca inuloides) - Nieto Ramírez, María Isabel; García Trejo, Juan Fernando; Caltzontzin Rabell, Valeria; Chávez Jaime, Ruth; Estrada Sánchez, María de la Luz (Revista Mexicana de Ciencias Agrícolas, 2018)
At present, Heterotheca inuloides or arnica for its common name, has been used for its anti-inflammatory activity, in addition, this plant has other applications as a treatment against rheumatism, gastrointestinal disorders, among others. These therapeutic properties are due to secondary metabolites such as phenols and flavonoids. The concentration of these compounds can be influenced by biotic or abiotic stress, where the culture conditions such as relative humidity, the temperature of the environment and even the type of irrigation, represent an abiotic stress. That is why the objective of this work is to compare different culture conditions on the production of phenols, total flavonoids and their antioxidant capacity in arnica (Heterotheca inuloides). To achieve this goal, arnica plants were commercially obtained, placing 14 plants in a greenhouse and 14 plants in open-pit culture. In addition, each of these farming systems had two types of irrigation systems, the first with water with nutrient solution and the second with aquaculture wastewater. Also, it was elicited with salicylic acid at the concentrations 0.0 mM, 0.5 mM and 1 mM, twice every 14 days. The concentration of phenols, total flavonoids and antioxidant capacity was determined before each elicitation. Maximum phenolic compounds were present in plants grown in the field, irrigated with nutrient solution and elicited at 0.5 mM. The total flavonoids and antioxidant activity were present in greenhouse plants, irrigated with nutrient solution, without effect on elicitation. According to some of the results obtained I know that it concludes that the cultivation conditions for the production of phenols are not different for the production of flavonoids and the antioxidant capacity of said compounds.
Keywords: antioxidant capacity; culture conditions; phenols; flavonoids